Cardioprotective effect of grape polyphenol extract against doxorubicin induced cardiotoxicity - Shynggys Sergazy (Nature Portfolio, 2020)
Abstract Doxorubicin is a chemotherapeutic agent known to cause cardiotoxicity that is thought to be associated with oxidative stress. The aim of the current study is to investigate the role of grape polyphenols’ antioxidant property as cardioprotective against doxorubicin-induced cardiotoxicity. Adult Wistar rats weighing 200 ± 20 g were divided into 3 different groups: a doxorubicin group that received a single intraperitoneal administration of doxorubicin (8.0 mg/kg body weight), an experimental group that received doxorubicin and grape polyphenol concentrate (25 mg/kg) via intragastric route, and the third group was a negative control group that received water only. On day 8, blood samples and tissues were harvested for analyses. The results indicated that grape polyphenol concentrate was able to reduce the signs of cardiotoxicity of doxorubicin through the reduction of aspartate aminotransferase activation, increasing the plasma antioxidant levels and decreasing the level of free radicals. The results also showed that grape polyphenol concentrate was able to reverse doxorubicin-induced microscopic myocardial damage. The myocardial protective effect of grape polyphenol might likely be due to the increase in the level and activity of the antioxidant enzymes, superoxide dismutase, catalase, and glutathione peroxidase. In conclusion, grape polyphenol concentrate displayed cardioprotective effect and was able to reverse doxorubicin-induced-cardiomyopathy in experimental rats.